Comparison of Cognitive Function Examination Using Montreal Cognitive Assessment (MOCA-INA) with Telephone Moca (T-MOCA) - Ristinawati, Ira; Fairuzya, Azmi Farah (Smart Medical Journal, 2022)
Introduction: The prevalence of dementia tends to increase over time. MOCA assessment tool is a cognitive function screening test that has high sensitivity. Telephone-based MOCA assessment has potential of detection and monitoring dementia which can be widely applied.Methods: This is an observational study with cross-sectional approach in the Neurology Outpatient Department RSUD Dr. Moewardi. The aim of this study is to compare the effectiveness of MOCA-INA assessment tool with the T-MOCA.Results: There were 424 patients who underwent MOCA-INA examination during January-June 2022. After screening, 185 patients were able to complete the study. Subjects consisted of 67 males (36.2%) and 118 females (63.8%); aged 65-74 years (44.9%), 75-84 years (25.9%), and 85 years (29.2%). It was found that the conformity diagnosis of MOCA-INA to T-MOCA was 82.3% in the conversion test. There were significant differences between normal patients and MCI patients in age (p=0.000), education level (p=0.000), MOCA-INA score (p=0.000), and T-MOCA score (p=0.000). The relationship between MOCA-INA and T-MOCA has a strong positive correlation (p = 0.000; r = 0.789). Subsequent correlation test between MOCA-INA and T-MoCA showed a strong significant relationship in the direction of gender (p = 0.000; r = 0.438) and education level (p = 0.000; r = -0.323)Conclusion: Both MOCA-INA and T-MOCA could significantly determine the level of cognitive function with a strong correlation between the two assessments.